Uji Kesesuaian CT Number Pada Pesawat CT Scan Multislice Di Rumah Sakit Sunset Vet Kuta - Ricky Richard Ivanson Tude; Aris Diartama; Made Purwa Darmita (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
This research was conducted to determine the accuracy and uniformity of CT Numbers from CT-Scan images using a phantom at Sunset Vet Hospital Kuta. This conformity test is carried out to ensure that the CT-Scan aircraft meets radiation safety requirements and provides precise and accurate diagnostic information. The method used is varying the thickness of the slice thickness, namely 3 mm, 5 mm, 8 mm and 10 mm, tube voltage 130 kVp, tube current 100 mA, window width 200 and window level 40 and ROI in the form of a circle with a size range of 1,000 – 1,005 cm2 in each slice thickness, there are 5 ROIs with different positions, namely middle ROI, ROI at 12 o'clock, ROI at 3 o'clock, ROI at 6 o'clock, and ROI at 9 o'clock. From the measurement results, the accuracy and uniformity values ​​of the CT Number are different for each slice and ROI position, for the tolerance limit for CT Number accuracy values ​​according to PERKA BAPETEN Number 2 of 2018 is in the range -4 to 4, while the tolerance limit for CT Number uniformity values ​​is in the range -2 to 2. From the results of measurements that have been carried out, the accuracy and uniformity values The CT Number in this study has passed the test. The research results show that slice thickness does not affect the accuracy and uniformity of the CT Number on CT-Scan images.